Microporous 3D aluminum MOF doped into chitosan‐based mixed matrix membranes for ethanol/water separation. Issue 9 (8th August 2019) - Vinu, Madhan; Pal, Souvik; Chen, Jia‐Dian; Lin, Yi‐Feng; Lai, Yu‐Lun; Lee, Cheng‐Shiuan; Lin, Chia‐Her
Abstract: An aluminum metal–organic framework (Al‐MOF), [Al(OH)(BPDC)] (DUT‐5; BPDC = Biphenyl‐4, 4′‐dicarboxylate), was synthesized using solvothermal reactions. The high surface area and micropores (approximately 1.2 nm) of DUT‐5 were characterized using N2 gas sorption measurements. The thermal stability of DUT‐5 and its phase purity were also investigated. The different amounts of DUT‐5 (0.1, 0.15, and 0.2 wt%) were successfully incorporated into the chitosan (CS) polymer to prepare a mixed matrix membrane (MMM) for the pervaporation of water/ethanol at 25°C. In particular, when 0.15 wt% of DUT‐5 was loaded, the DUT‐5@CS MMMs displayed excellent permeability and selectivity in ethanol/water separation. The results indicated that compared with pristine chitosan membranes, the flux of DUT‐5@CS membranes with 0.15 wt% loading significantly increased from 315 to 378 (g/m 2 h −1 ) and the separation factor from 347 to 3, 429. These promising results of the microporous Al‐MOF doped into chitosan MMMs reveal its good application potential for the bio‐ethanol separation processes. Abstract : This article presents a new combination of microporous MOF and chitosan membrane. In the MOF of DUT‐5, the stable and microporous framework can separate water from ethanol with a hydrophobicsite. The results demonstrate the possibility that MOF‐doped membrane with chitosan DUT‐5@CS MMMs that may serve as molecular sieves for biofuel production.